2019
DOI: 10.1002/lary.27889
|View full text |Cite
|
Sign up to set email alerts
|

Injection of bevacizumab and cyanoacrylate glue for hereditary hemorrhagic telangiectasia

Abstract: Objectives/Hypothesis The objective of this study was to report for the first time on the results of submucosal injections of bevacizumab used in conjunction with cyanoacrylate glue sclerotherapy in hereditary hemorrhagic telangiectasia (HHT). Study Design Retrospective analytic chart review. Methods We performed a chart review that included all patients with HHT treated with intranasal bevacizumab and cyanoacrylate glue for refractory epistaxis at Lariboisiere University Hospital from 2013 with a minimum foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…28 Khoueir et al used the Epistaxis Severity Score (mean reduction of 7.8 to 3.8, Bergler-Sadick Scale (mean frequency reduced from 2.74 to 1.64 and mean quantity from 2.54 to 1.51), and a Likert satisfaction score (mean improvement of 4.16 to 7.22) before and after treatment with cyanoacrylate glue and bevacizumab and found sclerotherapy alongside bevacizumab significantly effective in improving epistaxis (P < .05). 29 The study by Roux-Vaillard et al was split into 2 data sets because 2 separate patient cohorts were reported in that study. Roux-Vaillard et al 25 reported improvement in epistaxis frequency in all patients after Ethibloc injections with 55% of patients reporting decreased duration of epistaxis 1 month after the first injection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Khoueir et al used the Epistaxis Severity Score (mean reduction of 7.8 to 3.8, Bergler-Sadick Scale (mean frequency reduced from 2.74 to 1.64 and mean quantity from 2.54 to 1.51), and a Likert satisfaction score (mean improvement of 4.16 to 7.22) before and after treatment with cyanoacrylate glue and bevacizumab and found sclerotherapy alongside bevacizumab significantly effective in improving epistaxis (P < .05). 29 The study by Roux-Vaillard et al was split into 2 data sets because 2 separate patient cohorts were reported in that study. Roux-Vaillard et al 25 reported improvement in epistaxis frequency in all patients after Ethibloc injections with 55% of patients reporting decreased duration of epistaxis 1 month after the first injection.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review revealed marked variation in reporting epistaxis outcomes in HHT patients. The measure of epistaxis outcomes in 3 papers—Esteban-Casado et al, 28 Khoueir et al, 29 and Boyer et al 30 —was reported using the Epistaxis Severity Score, a validated scoring system published by Hoag et al based on review of HHT literature (Table 3). 31 The Epistaxis Severity Score has been validated both internally and externally via a survey of 900 people across 21 countries.…”
Section: Resultsmentioning
confidence: 99%
“…6 Although a randomized, controlled trial showed that topical bevacizumab spray had no advantage over saline con-trol, only retrospective studies or limited prospective studies were available to assess the potential benefit of submucosal injection of bevacizumab. 16,[26][27][28] In one such retrospective study, Simonds et al found that adding a 100-mg submucosal dose of bevacizumab after using a KTP laser for lesion photocoagulation reduced patient disability. 29 Riss et al performed a randomized, double-blind, placebocontrolled trial of submucosal injection of 100 mg bevacizumab at the single most affected mucosal area of the nose.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the existing literature in 2018 identified submucosal bevacizumab injection with or without laser treatment as an option in management of HHT‐related epistaxis, with potential benefits that outweighed the harms, although with unclear cost implications 6 . Although a randomized, controlled trial showed that topical bevacizumab spray had no advantage over saline control, only retrospective studies or limited prospective studies were available to assess the potential benefit of submucosal injection of bevacizumab 16,26–28 . In one such retrospective study, Simonds et al found that adding a 100‐mg submucosal dose of bevacizumab after using a KTP laser for lesion photocoagulation reduced patient disability 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of bevacizumab, the cost-effectiveness is favourable to polidocanol, though the injection of bevacizumab and cyanoacrylate glue sounds promising [17], showing improvement in 31 patients with moderate-severe epistaxis after a mean follow up of 26.6 months (interval from 9 to 56). From a baseline HHT-ESS of 7.8 before injection, it decreased to 3.8 after the treatments.…”
Section: Discussionmentioning
confidence: 99%